TAKSONOMI TRANSENDEN (PARADIGMA BARU TUJUAN PENDIDIKAN AGAMA ISLAM) - Heriadi, Heriadi (Bajang Institute, 2025)
The Taxonomy of the Objectives of Islamic Education in the Qur'anic Perspective. This study is initiated from a thought that